Cryptophyte and Photosynthetic Picoeukaryote Abundances in the Bransfield Strait during Austral Summer - Vladimir Mukhanov; Evgeny Sakhon; Alexander Polukhin; Vladimir Artemiev; Eugene Morozov; An-Yi Tsai (Water, 2022)
A remarkable shift in the species composition and size distribution of the phytoplankton community have been observed in coastal waters along the Antarctic Peninsula over the last three decades. Smaller photoautotrophs such as cryptophytes are becoming more abundant and important for the regional ecosystems. In this study, flow cytometry was used to quantify the smallest phytoplankton in the central Bransfield Strait and explore their distribution across the strait in relation to physical and chemical properties of the two major water masses: the warmer and less saline Transitional Zonal Water with Bellingshausen Sea influence (TBW), and the cold and salty Transitional Zonal Water with Weddell Sea influence (TWW). Pico- and nano-phytoplankton clusters were distinguished and enumerated in the cytograms: photosynthetic picoeukaryotes, cryptophytes (about 9 µm in size), and smaller (3 µm) nanophytoplankton. It was shown that nanophytoplankton developed higher abundances and biomasses in the warmer and less saline TBW. This biotope was characterized by a more diverse community with a pronounced dominance of Cryptophyta in terms of biomass. The results support the hypothesis that increasing melt-water input can potentially support spatial and temporal extent of cryptophytes. The replacement of large diatoms with small cryptophytes leads to a significant shift in trophic processes in favor of the consumers such as salps, which able to graze on smaller prey.